LONG-TERM OUTCOMES OF TUBERCULOUS PLEURISY TREATMENT WITH REGARD TO DIAGNOSTIC TECHNIQUE USED FOR PLEURAL EFFUSION SYNDROME DIAGNOSIS - Duzhyi, Ihor D.; Oleshchenko, Halyna P.; Psarova, Valentyna H. (Eastern Ukrainian medical journal, 2022)
Introduction. Despite the overall positive epidemiological trend, the burden of tuberculosis in Ukraine remains significant. The most common form of extrapulmonary TB is tuberculous pleurisy. The share of the latter in the structure of all tuberculosis forms is within 10–12% or more. The clinical picture of specific pleurisy is diverse, so its diagnosis is often complicated and ultimately leads to various negative consequences. The authors suggested using a diagnostic system based on ultrasound findings to detect pleural effusion syndrome. Methods. We examined 329 patients with tuberculous pleurisy, who were divided into two groups. There were 142 subjects in the main group and 187 subjects in the comparison group. The radiodiagnostic examination was based on traditional chest radiography. The patients of the main group were examined according to the pleural diseases diagnostic algorithm implemented by the fellows of the department (utility model patent of Ukraine No. 114430). Results. In the long-term period, residual changes (thickening) in the pleural cavity were found in 6.8% of patients in the main group vs. 19.8% of patients in the comparison group (p < 0.05), changes in diaphragmatic skeletopy were observed in 13.5% vs. 25.9%, respectively (p < 0.05), and diaphragmatic mobility disorder – in 5.4% vs. 18.5%, respectively (p < 0.05). Patients with tuberculous pleurisy who had been examined according to the proposed algorithm developed chronic pleurisy 7.1 times less often (1.4% vs. 9.9%, p < 0.05) and pulmonary disease – 2.7 times less often (4.1% vs. 11.1%, respectively, p ˃ 0.05). Conclusion. Taking into account the early detection of pleural effusion and timely verification of the disease, the proposed diagnostic algorithm for pleural diseases allows to reduce the long-term effects on the chest wall, lungs, and pleura.